Altered Gut Microbiota and Host Metabolite Profiles in Women With Human Immunodeficiency Virus. (21st November 2019) - Wang, Zheng; Usyk, Mykhaylo; Sollecito, Christopher C; Qiu, Yunping; Williams-Nguyen, Jessica; Hua, Simin; Gradissimo, Ana; Wang, Tao; Xue, Xiaonan; Kurland, Irwin J; Ley, Klaus; Landay, Alan L; et al.
Abstract: Background: Alterations in gut microbiota (GMB) and host metabolites have been noted in individuals with HIV. However, it remains unclear whether alterations in GMB and related functional groups contribute to disrupted host metabolite profiles in these individuals. Methods: This study included 185 women (128 with longstanding HIV infection, 88% under antiretroviral therapy; and 57 women without HIV from the same geographic location with comparable characteristics). Stool samples were analyzed by 16S rRNA V4 region sequencing, and GMB function was inferred by PICRUSt. Plasma metabolomic profiling was performed using liquid chromatography–tandem mass spectrometry, and 133 metabolites (amino acids, biogenic amines, acylcarnitines, and lipids) were analyzed. Results: Four predominant bacterial genera were identified as associated with HIV infection, with higher abundances of Ruminococcus and Oscillospira and lower abundances of Bifidobacterium and Collinsella in women with HIV than in those without. Women with HIV showed a distinct plasma metabolite profile, which featured elevated glycerophospholipid levels compared with those without HIV. Functional analyses also indicated that GMB lipid metabolism was enriched in women with HIV. Ruminococcus and Oscillospira were among the top bacterial genera contributing to the GMB glycerophospholipid metabolism pathway and showed positive correlations with host plasma glycerophospholipid levels. One bacterial functional capacity in the acetate and propionate biosynthesis pathway was identified to be mainly contributed by Bifidobacterium ; this functional capacity was lower in women with HIV than in women without HIV. Conclusions: Our integrative analyses identified altered GMB with related functional capacities that might be associated with disrupted plasma metabolite profiles in women with HIV. Abstract : We identified altered gut microbiota associated with disrupted plasma metabolite profiles in women with HIV. Two genera, Ruminococcus and Oscillospira, with functional capacities in the glycerophospholipid metabolism pathway were enriched, while Bifidobacterium, a probiotic genera, was depleted in these women.